A Gallium(III) Complex that Engages Protein Disulfide Isomerase A3 (PDIA3) as an Anticancer Target. (28th August 2020) - Yin, Hao‐Yan; Gao, Jiu‐Jiao; Chen, Xuemin; Ma, Bin; Yang, Zi‐Shu; Tang, Juan; Wang, Bing‐Wu; Chen, Tianfeng; Wang, Chu; Gao, Song; Zhang, Jun‐Long
Abstract: Gallium(III)‐based drugs have gained momentum in cancer therapy due to their iron‐dependent anticancer activity. Judicious choice of ligands is critical for improved oral bioavailability, antitumor efficacy, and distinct mechanisms from simple Ga III salts. We describe Ga III complexes with planar tetradentate salen ligands [salen=2, 3‐bis[(4‐dialkylamino‐2‐hydroxybenzylidene)amino]but‐2‐enedinitrile)] and labile axial solvent ligands, which display tumor growth inhibition in vitro and in vivo comparable to cisplatin. Confocal fluorescence microscopy, western blotting, mRNA profiling, chemical proteomics, and surface plasmon resonance (SPR) studies provide compelling evidence that PDIA3, a member of the protein disulfide isomerase (PDI) family involved in endoplasmic reticulum (ER) stress, is a direct target of Ga‐1 . This work offers a new route to designing and synthesizing Ga‐based drugs, and also reveals that PDIA3 is an important anticancer target. Abstract : Ga III complexes (Ga‐1 ) featuring planar tetradentate N2 O2 Salen ligands are shown to demonstrate anticancer activity both in vitro and in vivo. Extensive chemical biology approaches, including transcriptomic and proteomic studies, suggest that PDIA3, a member of the protein disulfide isomerase (PDI) family involved in the endoplasmic reticulum (ER) stress response, is a key anticancer target for Ga‐1 .